Towards Sustainable Open Heart Surgery in Zimbabwe - Machawira, Simukayi Percy; Muteweye, Wilfred; Mutetwa, Emmerson; Kajese, Shield (Frontiers in Pediatrics, 2022)
Open heart surgery has become more readily available worldwide especially in the West, whilst it remains an elusive mirage for the majority of the people in Sub-Saharan Africa and Zimbabwe in particular. Efforts to provide the service began in the 1950’s and were a regular service from 1989 to 2003. Zimbabwe went through a phase of political and economic turmoil and this denied the majority of patient’s meaningful service. The aim of this paper is to review the history and look at the obstacles that continue to make this goal difficult to achieve currently. Political and economic challenges remain the main obstacles, however, countries in a similar predicament in Africa such as Ghana have been able to sustain their programs. Paramount to this is the requisite personnel, equipment consumables and competitive remuneration. It is our aim to work with the Government, private sector and other players to harness the country towards sustainable open heart surgery in Zimbabwe.